Analysis of Nusaniwe Peninsula Ecotourism Management : Sustainable Ecotourism Management Strategies in Ambon City, Indonesia - Dientje Rumerung; Steven Siaila (Khazanah Sosial, 2023)
Ecotourism is tourism development that prioritizes the sustainability of tourist objects in a sustainable manner that arises as a response to natural conditions that experience over-exploitation and are uncontrollable which cause damage to tourist objects that threaten their sustainability. Ecotourism is a form of tourism that takes place at tourist objects without damaging or disturbing the sustainability of these tourism objects. Semenanjung Nusaniwe is in Nusaniwe District in Ambon City, has more than 22 tourist objects that have been developed but have not been touched by development. Such conditions require analysis that will guide future developments. This writing is based on the results of research on 225 respondents to visitors to tourist attractions, as well as people who live around tourist attractions. The analysis used is the pattern of estimating the economic value of ecotourism based on the travel cost method (TCM). The determination of the socio-economic factors that affect the cost of travel to the Nusaniwe Peninsula area is tested using the Linear Regression Method. The results of the study show that many tourist objects in Nusaniwe District have been identified, and some have not been identified. This tourism object is always visited by the community and can generate income. The highest consumer surplus value is in the Tanjung Batu Konde Beach Tourist Attraction Object (ODTW), which is IDR. 208,355.00, and the lowest is at Sumber Jaya Beach, namely IDR. 12,545.50. The highest total economic value is in Tanjung Batu Konde, namely IDR. 352,033,800.00, and the lowest is also found at Sumber Jaya Beach, namely IDR. 8,480,758.00. Starting from the results of the calculations above, it can be concluded that if the tourism objects in Nusaniwe Sub district can be well developed, it is certain that each OTDW will be able to contribute to increasing income for the community around the tourist attraction as well as for the Village Government, State Government and even the City Government.